(untitled) (Research, Society and Development, 2021)
The question that moves this text is “How can school promote equal opportunities for children and adolescents?” In order to answer this question, we dialogue (bibliographically theoretical) with some philosophers of school education. We start from the assumption that all students have their own abilities to learn what is taught in school – the subject – and, therefore, we approach that equality must be a pedagogical principle. In order to exemplify the experience of the equality of intelligences in education we present two ways of being a teacher that seeks the intellectual emancipation of students: the ignorant teacher and the inventor teacher.